Overview Of Criminal Law Against The Crime Of Law Of Minor Child (Case Study At Polres Wonosobo) - Maulana, Ajmal (CV. Inara, 2022)
The crime of obscenity is part of the crime against decency. Where obscene acts do not only occur in adults but also occur in minors. Either directly or indirectly, children who are victims of sexual abuse crimes experience various disturbances to themselves, both physical and non-physical, resulting from these events. In writing this thesis (the author discusses the problem of the factors that cause the occurrence of crimes of sexual abuse against minors and efforts to prevent and overcome them.Perpetrators of crimes of sexual abuse against minors in committing a crime are carried out in various ways to fulfil or achieve their sexual desires, not only children who are victims but children can sometimes become perpetrators of sexual abuse. The author concludes that the factors that can increase and influence the occurrence of criminal acts of sexual abuse against minors are environmental factors, cultural factors, economic factors, media factors, and psychological or psychological factors of the perpetrators.